Sheet metal forming technology : recent developments, failure analysis, F.E. simulation, benchmarking and validation - Augusto Duarte Campos Barata da Rocha (2006)
Sheet Metal Forming Technology is nowadays facing important challenges related to the use of new materials and the drive to new or alternative industrial processes. This paper describes some research activity carried out at the Sheet Metal Forming Center of the University of Porto. The projects in which such research is included are related with both numerical and experimental works and they correspond to research areas related with Failure Prediction, Finite Element Simulation and experimental validation through benchmarking.